Effect of Soaking Time on the Physicochemical Characteristics, Antioxidant Activity, and Glycemic Index of Parboiled Local Cultivar Black Rice from West Sumatra - Nasution, Saidah Nauli; Nazir, Novizar; Wellyalia, Wellyalina; Azmi, Aida Firdaus Muhammad Nurul; Hariry, Amelia (Department of Technology of Agricultural product (THP) Jambi University, 2023)
Black rice, originating from Sariak Alahan Tigo in Solok Regency, is one of the indigenous rice varieties found in West Sumatra. Black rice is a cereal variety that has a low glycemic index and is rich in phytochemical substances called anthocyanins. These compounds act as antioxidants, helping to prevent diabetes and preserve the cardiovascular system. The procedure of parboiling involves varying the period of grain soaking in order to maximize the health advantages of anthocyanins found in black rice. The study utilized a completely randomized design (CRD) consisting of 5 treatments and 3 duplicates. The treatment protocol utilized in this experiment consisted of A (control), B (grain immersion for 2 hours), C (grain immersion for 3 hours), D (grain immersion for 4 hours), and E (grain immersion for 5 hours). The data acquired were evaluated using analysis of variance (ANOVA) and subsequently subjected to Duncan's Multiple Range (DNMRT) analysis at a significance level of 5%. The study findings indicate that the duration of grain soaking has a notable impact on various factors, including water content, starch levels, amylose and amylopectin levels, antioxidant activity, starch digestibility (in vitro), glycemic index values, taste, and texture. Nevertheless, the duration of grain soaking does not have any discernible impact on the physical hue, sensory hue, or fragrance of parboiled black rice. The treatment that is most favored according to the results of the sensory study is treatment D, which has a color rating of 3.86 (like), a fragrance rating of 3.91 (like), a taste rating of 3.91 (like), and a texture rating of 3.81 (like).